Organoids in cancer therapies: a comprehensive review - Xin-Yi, Jiang; Yan-Ran, Wang; Pin-Ru, Di; Shi-Yi, Qian; Hai-Tao, Jiang (Frontiers in Bioengineering and Biotechnology, 2025)
Organoid technology has significantly advanced biomedical research, offering deep insights into tumor biology and therapeutic efficacy. While existing publications have covered organoid applications, this review uniquely stresses their transformative role in cancer research. We highlight their importance in studying intratumoral heterogeneity and microenvironment interactions. Our analysis addresses knowledge gaps by detailing how organoids function as models in cancer initiation, drug screening, target identification, and sensitivity assessment. We also explore their applications in personalized medicine, such as developing patient-derived models for treatment prediction and immune therapy evaluation. This review discusses the latest progress in using organoids for cancer treatment, like predicting patient responses to precision medicine. However, challenges remain, including maintaining genetic stability and mimicking in vivo conditions. By addressing these limitations, this review provides a novel perspective on how organoid technology may overcome current barriers and drive innovation in cancer therapy. Our analysis suggests that advancements in organoid systems could enhance personalized treatment strategies and improve oncology patient outcomes.